Knee Arthroplasty New and Future Directions - Sharma, Mrinal; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book offers a comprehensive guide to knee arthroplasty that will assist in achieving excellent outcomes based on a sound understanding and technique. An introductory section on the primary knee arthroplasty that covers preoperative planning, surgical exposures, step by step approach to knee arthroplasty, unicondylar knee arthroplasty and radiological assessment are discussed in detail. The next section is devoted to topics pertaining to knee replacement in complex situations like bone defects, stiff knees, previous failed trauma and extra-articular deformities. A separate section has been dedicated to use of technology like Computer navigation and Robotics in TKA. An extensive section explains the causes and management of potential complications, including instability, infections, and periprosthetic fracture. Individual chapters focussing on multimodal pain management, deep vein thrombosis, rehabilitation and newer advances have been included .The surgical techniques appropriate for revision knee arthroplasty are described separately, and guidelines on how to deal with bone loss, instability, gap balancing, joint line restoration, and use of bulk allografts, hinges and condylar replacement prosthesis are provided. The authors are all respected experts from the United Kingdom, United States,India and Europe. The language of the book is easy to read, user friendly with colourful pictorial representation of relevant surgical steps. Case based discussions, surgical tips and pearls and summary has been added in each chapter. The references given at the end of each chapter would be useful for those doing research. This book should be of interest to practicing orthopaedic surgeon across the globe, beginner arthroplasty surgeons, postgraduate students of orthopaedics, DNB students and those preparing for board exams. This book will serve as a reference book for Master Arthroplasty surgeons as well as a compendium on Knee Arthroplasty.
SECTION I : PRIMARY TOTAL KNEE ARTHROPLASTY -- Chapter 1:Preoperative Planning in Primary Total Knee Arthroplasty -- Chapter 2: Surgical Exposures In Total Knee Arthroplasty -- Chapter 3: Implant Evolution and Design Rationale in Total Knee Arthroplasty -- Chapter 4: Basics in Total Knee Arthroplasty: a step by step approach to a varus knee -- Chapter 5: Total Knee Arthroplasty In Knees With Fixed Flexion Deformity -- Chapter 6: Total knee replacement in a valgus arthritic knee -- Chapter 7: Mobile Bearing Unicompartmental Knee Arthroplasty -- Chapter 8: Fixed Bearing Unicondylar Knee Arthroplasty -- Chapter 9: Radiological Assessment Of Total Knee Arthroplasty -- SECTION II : TOTAL KNEE ARTHROPLASTY IN COMPLEX PRIMARY SITUATIONS -- Chapter 10: Total Knee Arthroplasty In Stiff/Ankylosed Knees -- Chapter 11: Total Knee Arthroplasty in Extra-Articular Deformity -- Chapter 12: Post High Tibial Osteotomy Total Knee Arthroplasty -- Chapter 13: Total knee Arthroplasty in osteoarthrosis complicated with stress Fractures -- Chapter 14: Management of Bone Defects in Primary Total Knee Arthroplasty -- Chapter 15: Total Knee Arthroplasty in Morbidly Obese -- Chapter 16: Total Knee Arthroplasty in Post-trauma and Failed fixations -- Chapter 17: Sliding Condylar Osteotomy for Managing Severe Deformities in Total Knee Arthroplasty -- Chapter 18: Total Knee Arthroplasty In Genu Recurvatum -- Chapter 19: Total Knee Arthroplasty in Persons with Haemophilia -- Chapter 20: Total Knee Arthroplasty In Patient With History Of Previous Knee Sepsis -- SECTION III : MANAGING COMPLICATIONS POST TOTAL KNEE ARTHROPLASTY -- Chapter 21: Periprosthetic Fractures following Total Knee Replacement -- Chapter 22: Management of Extensor Mechanism Disruption in Total Knee -- Chapter 23: Painful Total Knee Arthroplasty :an algorithmic approach -- Chapter 24: Management of The Stiff Total Knee Replacement -- Chapter 25: Knee Prosthetic Instability -- Chapter 26: Periprosthetic Joint Infection - Diagnosis and principles of management -- Chapter 27: D.A.I.R : Concept and Results -- Chapter 28: Single Stage Revision Total Knee Arthroplasty for Periprosthetic -- Chapter 29: Revision for Infected Total Knee Replacement -- SECTION IV : TECHNOLOGY IN TOTAL KNEE ARTHROPLASTY -- Chapter 30: The Science Behind Computer Assisted Surgery Of The Knee -- Chapter 31: Computer assisted total knee arthroplasty: a step wise approach -- Chapter 32: Navigation Assisted Unicondylar Knee Replacement -- Chapter33: Patient Specific Instrumentation in Total Knee Arthroplasty -- Chapter 34: Overview of Robotics in Total Knee Arthroplasty -- Chapter 35: Total Knee Arthroplasty using robotics (MAKO) -- Chapter 36: Robotic Assisted Unicondylar Knee Arthroplasty -- Chapter 37: Fast Track Total Knee Arthroplasty -- SECTION V : REVISION TOTAL KNEE ARTHROPLASTY -- Chapter 38: Mechanisms of failure in total knee arthroplasty: diagnosis & evaluation -- Chapter 39: Exposure Options in Revision Total Knee Arthroplasty -- Chapter 40: Prosthesis extraction in Revision Total Knee Arthroplasty -- Chapter 41: Prosthesis selection and rationale for use in revision total knee arthroplasty -- Chapter 42: Management of bone defects in revision total knee arthroplasty -- Chapter 43: Managing bone defects in Revision total knee replacement: concept and use of tantalum cones -- Chapter 44: Gap Balancing In Revision Total Knee Arthroplasty -- Chapter 45: Joint line Restoration in Revision Total knee Arthroplasty -- Chapter 46: Rotating Hinge knee in Primary and Revision knee Arthroplasty -- Chapter 47: Revision of Failed Unicondylar Knee Arthroplasty To A Total Knee Arthroplasty -- Chapter 48: Re-Revision Of A Previously Revised Total Knee Arthroplasty -- Chapter 49: Chapter 49: Bulk Allografts in Revision Total Knee Arthroplasty -- Chapter 50 : Condylar Replacement Prosthesis as a salvage in Knee Arthroplasty -- SECTION VI : ADVANCES IN PERIOPERATIVE MANAGEMENT IN TOTAL KNEE ARTHROPLASTY -- Chapter 51: Managing Soft Tissue Deficiencies In Total Knee Arthroplasty -- Chapter 52: Multimodal Pain Management in Total knee Arthroplasty -- Chapter 53: Deep Vein Thrombosis: Prophylaxis And Management -- Chapter 54: Optimal Rehabilitation after Total Knee Arthroplasty.
Keywords: Orthopedics; Orthopaedics; Arthroplasty, Replacement, Knee; Outcome Assessment, Health Care